Evidence for a Dualistic Model of High-grade Serous Carcinoma: BRCA Mutation Status, Histology, and Tubal Intraepithelial Carcinoma. (March 2015) - Howitt, Brooke E.; Hanamornroongruang, Suchanan; Lin, Douglas I.; Conner, James E.; Schulte, Stephanie; Horowitz, Neil; Crum, Christopher P.; Meserve, Emily E.
Abstract : Most early adnexal carcinomas detected in asymptomatic women with germline BRCA mutations ( BRCA + ) present as serous tubal intraepithelial carcinomas (STIC). However, STICs are found in only ∼40% of symptomatic high-grade serous carcinomas (HGSCs) and less frequently in pseudoendometrioid variants of HGSC. Consecutive cases of untreated HGSC from BRCA + and BRCA − women with detailed fallopian tube examination (SEE-FIM protocol) were compared. STIC status (+/−) was determined, and tumors were classified morphologically as SET ("SET", >50% solid, pseudoendometrioid, or transitional) or classic predominate ("Classic"). SET tumors trended toward a higher frequency in BRCA + versus BRCA − women (50% vs. 28%, P =0.11), had a significantly younger mean age than those with classic HGSC in BRCA − women (mean 56.2 vs. 64.8 y, P =0.04), and displayed a better clinical outcome in both groups combined ( P =0.024). STIC was significantly more frequent in tumors from the BRCA − cohort (66% vs. 31%, P =0.017) and specifically the BRCA − tumors with classic morphology (83%) versus those with SET morphology (22%, P =0.003). Overall, several covariables—histology, BRCA status, age, coexisting STIC, and response to therapy—define 2 categories of HGSC with differences in precursor (STIC) frequency, morphology, and outcome. We introduce a dualistic HGSC model that could shed light on the differences in frequency of STIC between symptomatic and asymptomatic women with HGSC. This model emphasizes the need for further study of HGSC precursors to determine their relevance to the prevention of this lethal malignancy.